Optical adhesive and preparation method thereof
By using combinations of raw materials such as acrylate prepolymers and ultraviolet irradiation and stirring steps in OCA optical glue, the problems of insufficient optical adhesiveness and low light transmittance are solved, and high viscosity, low haze and high stability are achieved The preparation of optical glue improves production efficiency and service life.
Patent Information
- Application Number
- CN202411497296.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-17
AI Technical Summary
The surface of the existing OCA optical film is insufficient, and it is easy to leave traces when peeled off. It is easy to produce bubbles and dust adsorption during bonding. It has low adhesion, low light transmittance, and has curing and shrinking, low production efficiency and high process cost.
Using an optical glue preparation method, including acrylate prepolymer, diluent, acrylic acid, isobornyl methacrylate, silica sol, initiator, crosslinking agent and antioxidant, through ultraviolet light irradiation and stirring steps, Optical glue with high viscosity, low haze and high transparency.
It improves the viscosity and peelability of optical adhesives, enhances light transmittance and stability, reduces curing and shrinkage, improves weather resistance and service life, and reduces process costs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of OCA optical adhesives, and more specifically relates to an optical adhesive and a preparation method thereof. Background Art
[0002] Optical adhesive can be applied to different fields according to its thickness. Its main uses are: electronic paper, transparent device bonding, projection screen assembly, aerospace or military optical device assembly, display assembly, lens assembly, resistive touch screen G+F+F, F+F, capacitive touch screen, panel, ICON and glass and polycarbonate and other plastic materials bonding.
[0003] OCA (Optically Clear Adhesive) is a special adhesive used to bond transparent optical components (such as lenses, etc.). It is required to be colorless and transparent, have high light transmittance, a certain bonding strength, can be cured at room temperature or medium temperature, and have small curing shrinkage. OCA optical adhesive is one of the important raw materials for touch screens. It is made by making optical acrylic adhesive without a substrate, and then bonding a layer of release film to the upper and lower bottom layers. It is a double-sided bonding tape without a substrate material. OCA adhesive can be used to bond the touch screen and the display screen, eliminating the air layer between the touch screen and the display screen, thereby improving the display effect and isolating dust and water vapor.
[0004] However, the current OCA film surface is sticky, and it is easy to leave marks on the surface when peeling off the release film. It is easy to generate bubbles, absorb dust and impurities, and leave residual adhesive when laminating. OCA has weak adhesive performance and low adhesion. There is a risk of rebound for products with high lamination requirements. After lamination, the light transmittance is not high enough and shrinkage occurs, resulting in low production efficiency and high process costs.
[0005] Therefore, how to provide an optical adhesive and a preparation method thereof is a problem that those skilled in the art need to solve urgently. Summary of the invention
[0006] In order to overcome the shortcomings and deficiencies in the prior art, the present invention provides an optical adhesive and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] An optical adhesive comprises the following raw materials, measured by weight: 75-100 parts of acrylate prepolymer, 15-30 parts of diluent, 5-8 parts of acrylic acid, 10-20 parts of isobornyl methacrylate, 10-20 parts of silica sol, 2-3 parts of initiator, 0.5-3 parts of crosslinking agent, and 0.5-3 parts of antioxidant;
[0009] The acrylic resin is polymerized by hard monomers, soft monomers and functional monomers under the action of a photoinitiator.
[0010] Preferably, the mass ratio of the hard monomer, the soft monomer, the functional monomer and the photoinitiator is 20-45:50-60:5-15:0.5-1.
[0011] Preferably, the hard monomer is selected from one or more of methyl acrylate, ethyl methacrylate, methyl methacrylate, n-butyl methacrylate, and dimethylaminoethyl methacrylate;
[0012] The soft monomer is selected from one or more of butyl acrylate, isooctyl acrylate, isobutyl acrylate, sec-butyl acrylate, n-propyl acrylate, lauryl methacrylate, tridecyl methacrylate, and 2-hexylhexyl methacrylate;
[0013] The functional monomer is selected from one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, acrylamide, N-vinyl cyclohexylamide, maleic anhydride, and glycidyl methacrylate;
[0014] The photoinitiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisocyanate.
[0015] Preferably, the diluent is selected from one or more of hydroxyethyl methacrylate, tripropylene glycol diacrylate, isooctyl acrylate, tetrahydrofurfuryl acrylic acid, hexanediol dimethacrylate, polyethylene glycol diacrylate, trimethylolpropane tri(meth)acrylate, and tetrapentaerythritol triacrylate.
[0016] Preferably, the initiator is selected from one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzophenone, and 2,2-diethoxyacetophenone.
[0017] Preferably, the cross-linking agent is selected from one or more of triethylenetetramine and toluene diisocyanate.
[0018] Preferably, the antioxidant is selected from one or more of thiophosphoryl disulfide, dialkyl phosphite, and triisooctyl phosphite.
[0019] The present invention also provides a method for preparing the above optical adhesive, comprising the following steps:
[0020] (1) adding a hard monomer, a soft monomer, a functional monomer, and a photoinitiator into a reaction kettle according to a mass ratio, stirring them uniformly under the protection of a nitrogen atmosphere, and irradiating them with ultraviolet light to cause a free radical polymerization reaction to obtain an acrylate prepolymer;
[0021] (2) Adding a diluent, acrylic acid, isobornyl methacrylate, silica sol, an initiator, a crosslinking agent, and an antioxidant to the acrylate prepolymer in parts by weight, stirring the mixture, and obtaining an optical adhesive.
[0022] Preferably, the wavelength of the ultraviolet light in step (1) is 150-300 nm.
[0023] Preferably, the stirring temperature in step (2) is 40-45° C. and the stirring time is 1-2 h.
[0024] It can be seen from the above technical solutions that, compared with the prior art, the present invention provides an optical adhesive and a preparation method thereof, which has the following beneficial effects:
[0025] (1) The optical adhesive prepared by the present invention has good adhesion, is not easy to leave residual adhesive on the bonding display material, has high elongation, and has good peeling properties. At the same time, the polymerization of various raw materials improves the transmittance and stability of the optical adhesive, which is highly transparent, low haze, has no shrinkage during curing, and has good weather resistance.
[0026] (2) The present invention contains a certain amount of isobornyl methacrylate, which has a high boiling point and flash point, strong structural stability, and can improve the stability of the optical adhesive. Isobornyl methacrylate is also highly viscous and can produce an adhesive effect on the remaining components, thereby exerting an adhesive effect and improving the stability of the optical adhesive. The present invention also adds silica sol, which does not react with any substance except strong alkali and hydrofluoric acid. It can still maintain stable chemical properties when in contact with oxygen or ultraviolet rays, greatly improving the stability of the optical adhesive and slowing down the yellowing rate of the optical adhesive. At the same time, silica sol has many micropores, good adsorption and adhesion, and can also improve the thermal stability, chemical stability and mechanical strength of the material, thereby increasing the service life of the OCA optical adhesive. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] An optical adhesive, comprising the following raw materials, by weight: 75 parts of acrylate prepolymer, 15 parts of hydroxyethyl methacrylate, 5 parts of acrylic acid, 10 parts of isobornyl methacrylate, 10 parts of silica sol, 2 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.5 parts of toluene diisocyanate, and 0.5 parts of dialkyl phosphite;
[0030] The mass ratio of ethyl methacrylate, butyl acrylate, methacrylic acid and azobisisobutyronitrile is 20:50:5:0.5.
[0031] A method for preparing an optical adhesive comprises the following steps:
[0032] (1) adding ethyl methacrylate, butyl acrylate, methacrylic acid, and azobisisobutyronitrile into a reaction kettle according to a mass ratio, stirring evenly under the protection of a nitrogen atmosphere, and irradiating with ultraviolet light having a wavelength of 300 nm to cause a free radical polymerization reaction to obtain an acrylate prepolymer;
[0033] (2) Add hydroxyethyl methacrylate, acrylic acid, isobornyl methacrylate, silica sol, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, toluene diisocyanate, and dialkyl phosphite to the acrylate prepolymer in parts by weight, and stir at a temperature of 40° C. for 2 hours to obtain an optical adhesive.
[0034] Example 2
[0035] An optical adhesive, comprising the following raw materials, by weight: 100 parts of acrylate prepolymer, 30 parts of hydroxyethyl methacrylate, 8 parts of acrylic acid, 20 parts of isobornyl methacrylate, 20 parts of silica sol, 3 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 3 parts of toluene diisocyanate, and 3 parts of dialkyl phosphite;
[0036] The mass ratio of ethyl methacrylate, butyl acrylate, methacrylic acid and azobisisobutyronitrile is 45:60:15:1.
[0037] The preparation method of the optical adhesive is the same as that of Example 1.
[0038] Example 3
[0039] An optical adhesive, comprising the following raw materials, by weight: 80 parts of acrylate prepolymer, 20 parts of hydroxyethyl methacrylate, 6 parts of acrylic acid, 15 parts of isobornyl methacrylate, 15 parts of silica sol, 2.5 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1 part of toluene diisocyanate, and 1 part of dialkyl phosphite;
[0040] The mass ratio of ethyl methacrylate, butyl acrylate, methacrylic acid and azobisisobutyronitrile is 30:55:10:0.8.
[0041] The preparation method of the optical adhesive is the same as that of Example 1.
[0042] Example 4
[0043] An optical adhesive, comprising the following raw materials, by weight: 80 parts of acrylate prepolymer, 20 parts of tripropylene glycol diacrylate, 6 parts of acrylic acid, 15 parts of isobornyl methacrylate, 15 parts of silica sol, 2.5 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 1 part of triethylenetetramine, and 1 part of triisooctyl phosphite;
[0044] The mass ratio of dimethylaminoethyl methacrylate, lauryl methacrylate, glycidyl methacrylate and dimethyl azobisisopropylate is 30:55:10:0.8.
[0045] (1) adding dimethylaminoethyl methacrylate, lauryl methacrylate, glycidyl methacrylate, and dimethyl azobisisocyanate into a reaction kettle according to a mass ratio, stirring the mixture evenly under the protection of a nitrogen atmosphere, and irradiating the mixture with ultraviolet light having a wavelength of 300 nm to cause a free radical polymerization reaction to obtain an acrylate prepolymer;
[0046] (2) Add tripropylene glycol diacrylate, acrylic acid, isobornyl methacrylate, silica sol, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, triethylenetetramine, and triisooctyl phosphite to the acrylate prepolymer in parts by weight, stir at 40°C for 2 hours to obtain an optical adhesive.
[0047] Example 5
[0048] An optical adhesive, comprising the following raw materials, by weight: 80 parts of acrylate prepolymer, 20 parts of hexanediol dimethacrylate, 6 parts of acrylic acid, 15 parts of isobornyl methacrylate, 15 parts of silica sol, 2.5 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 1 part of toluene diisocyanate, and 1 part of thiophosphoryl disulfide;
[0049] The mass ratio of n-butyl methacrylate, 2-hexylhexyl methacrylate, acrylamide and azobisisoheptanenitrile is 30:55:10:0.8.
[0050] (1) adding n-butyl methacrylate, 2-hexyl methacrylate, acrylamide, and azobisisoheptanenitrile into a reaction kettle according to a mass ratio, stirring the mixture evenly under a nitrogen atmosphere, and irradiating the mixture with ultraviolet light having a wavelength of 300 nm to cause a free radical polymerization reaction, thereby obtaining an acrylate prepolymer;
[0051] (2) Add hexanediol dimethacrylate, acrylic acid, isobornyl methacrylate, silica sol, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, toluene diisocyanate, and thiophosphoryl disulfide to the acrylate prepolymer in parts by weight, and stir at a temperature of 40° C. for 2 hours to obtain an optical adhesive.
[0052] Comparative Example 1
[0053] The difference from Example 3 is that isobornyl methacrylate is not added, and the rest is the same. An optical adhesive is obtained.
[0054] Comparative Example 2
[0055] The difference from Example 3 is that no silica sol is added, and the rest is the same. An optical adhesive is obtained.
[0056] Comparative Example 3
[0057] The difference from Example 3 is that the mass fraction of acrylic acid is 10 parts.
[0058] Comparative Example 4
[0059] The difference from Example 3 is that no acrylate prepolymer is added, and the rest is the same. An optical adhesive is obtained.
[0060] The prepared optical adhesive was coated on release films respectively, and cured by ultraviolet light to obtain an optical adhesive film with a thickness of 100 μm, which was then tested. The results are shown in Table 1.
[0061] Among them, peel strength test: transfer the film to the PET film and measure the 180° peel strength of the pressure-sensitive adhesive tape. The test standards and methods refer to GB / T 7122-1996.
[0062] Residual adhesive test: transfer the adhesive film to the PET film, attach it to the glass, press it back and forth naturally with a 2kg roller, let it stand for 20 minutes, gently tear off the adhesive film to see if there is any adhesive residue on the adhesive material.
[0063] Elongation at break test: refer to GB / T 30776-2014.
[0064] Shrinkage test: Apply the glue to the release film, let it stand for 10 minutes, and observe whether the uncured film area shrinks.
[0065] Table 1
[0066] Group Transmittance % Refractive index % Peel force g / 25mm Elongation at break % Is there any residual glue? Whether to shrink Example 1 95.7 1.488 2086 600 No residual glue No shrinkage Example 2 96.4 1.486 2137 860 No residual glue No shrinkage Example 3 97.8 1.481 2472 950 No residual glue No shrinkage Example 4 95.1 1.483 2246 760 No residual glue No shrinkage Example 5 93.6 1.482 2049 820 No residual glue No shrinkage Comparative Example 1 91.2 1.480 1623 320 Residual Glue shrink Comparative Example 2 93.5 1.482 1358 400 Residual Glue shrink Comparative Example 3 92.6 1.481 1531 240 Residual Glue shrink Comparative Example 4 92.9 1.486 1154 120 Residual Glue shrink
[0067] As can be seen from Table 1, when isobornyl methacrylate or silica sol is not present, the bonding force between the raw materials decreases, the peeling force is small, and the stability of the optical adhesive is poor. An appropriate amount of acrylic acid increases the interaction force between molecules, and also increases the rigidity of the molecular chain, increases the cohesive force of the polymer, and has good viscosity without affecting the peeling force. When the amount of acrylic acid is excessive, the viscosity of the optical adhesive decreases and the peeling force decreases. The optical adhesive prepared by the present invention has good viscosity, is not easy to leave residual glue on the bonding display material, has high elongation, and has good peeling properties. At the same time, the polymerization of the raw materials improves the light transmittance and stability of the optical adhesive, which is highly transparent, low haze, has no shrinkage during curing, and has good weather resistance.
[0068] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the scheme disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0069] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An optical adhesive, characterized in that: The raw materials include the following by weight: 75-100 parts of acrylate prepolymer, 15-30 parts of diluent, 5-8 parts of acrylic acid, 10-20 parts of isobornyl methacrylate, 10-20 parts of silica sol, 2-3 parts of initiator, 0.5-3 parts of crosslinking agent, and 0.5-3 parts of antioxidant; The acrylic resin is polymerized by hard monomers, soft monomers and functional monomers under the action of a photoinitiator.
2. The optical adhesive according to claim 1, characterized in that: The mass ratio of the hard monomer, the soft monomer, the functional monomer and the photoinitiator is 20-45:50-60:5-15:0.5-1.
3. The optical adhesive according to claim 1, characterized in that: The hard monomer is selected from one or more of methyl acrylate, ethyl methacrylate, methyl methacrylate, n-butyl methacrylate, and dimethylaminoethyl methacrylate; The soft monomer is selected from one or more of butyl acrylate, isooctyl acrylate, isobutyl acrylate, sec-butyl acrylate, n-propyl acrylate, lauryl methacrylate, tridecyl methacrylate, and 2-hexylhexyl methacrylate; The functional monomer is selected from one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, acrylamide, N-vinyl cyclohexylamide, maleic anhydride, and glycidyl methacrylate; The photoinitiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisocyanate.
4. The optical adhesive according to claim 1, characterized in that: The diluent is selected from one or more of hydroxyethyl methacrylate, tripropylene glycol diacrylate, isooctyl acrylate, tetrahydrofurfuryl acrylate, hexanediol dimethacrylate, polyethylene glycol diacrylate, trimethylolpropane tri(meth)acrylate, and tetrapentanol triacrylate.
5. The optical adhesive according to claim 1, characterized in that: The initiator is selected from one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzophenone, and 2,2-diethoxyacetophenone.
6. The optical adhesive according to claim 1, characterized in that: The cross-linking agent is selected from one or more of triethylenetetramine and toluene diisocyanate.
7. The optical adhesive according to claim 1, characterized in that: The antioxidant is selected from one or more of thiophosphoryl disulfide, dialkyl phosphite, and triisooctyl phosphite.
8. A method for preparing an optical adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) adding a hard monomer, a soft monomer, a functional monomer, and a photoinitiator into a reaction kettle according to a mass ratio, stirring them uniformly under the protection of a nitrogen atmosphere, and irradiating them with ultraviolet light to cause a free radical polymerization reaction to obtain an acrylate prepolymer; (2) Adding a diluent, acrylic acid, isobornyl methacrylate, silica sol, an initiator, a crosslinking agent, and an antioxidant to the acrylate prepolymer in parts by weight, stirring the mixture, and obtaining an optical adhesive.
9. The method for preparing an optical adhesive according to claim 8, characterized in that: The wavelength of the ultraviolet light in step (1) is 150-300nm.
10. The method for preparing an optical adhesive according to claim 8, characterized in that: The stirring temperature in step (2) is 40-45° C. and the stirring time is 1-2 h.
Citation Information
Cited By
A hydroxyl polythiaether-acrylic derivative, an ocr optical adhesive comprising the same, and a preparation method and application thereof
CN122978442A
